Reconstructing social theory, history and practice - Dahms, Harry F.; Lybeck, Eric Royal (Current perspectives in social theory ;, 2016)
With regard to developments in social theory, the past 30 years can be characterized as an Age of Deconstruction. Inspired by post-structuralism, postmodernism, critical theory, and science studies, as well as combinations of related approaches, theorists have endeavored to shatter historical meta-narratives and struggled to include previously excluded standpoints in social thought. This important trend has informed our understanding of the role of discourse, difference and expertise in determining relations of power and inequality. This volume focusses on "Reconstruction", dedicated to taking account of and interrogating the possibility of picking up the pieces. The papers were presented at the 2015 International Social Theory Consortium (ISTC). It considers questions such as, are there limits to the deconstruction project, and have these limits been reached? What are the possibilities for the reconstruction of narratives of long-term historical change? Is it possible to include and integrate the insights and contribution of various critiques of knowledge, while at the same time developing new forms of knowledge?